2014
DOI: 10.1016/j.ultrasmedbio.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Enhancement of Renal Parenchymal Masses with Contrast-Enhanced Ultrasound

Abstract: The purpose of this study was to investigate the value of quantitative assessment of enhancement in diagnosing renal cell carcinoma (RCC) with contrast-enhanced ultrasound (CEUS). A total of 73 solid renal parenchymal masses underwent both conventional ultrasound and CEUS. We compared the difference in maximum diameters on conventional ultrasound and CEUS between the benign and malignant groups. Enhancement features derived from a time-intensity curve were also analyzed. The diameters of renal cancer were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 13 publications
0
19
0
4
Order By: Relevance
“…The second criterion evaluated the lesion as a whole at 60 s post-injection; this was termed the ''washout phase,'' a time point not to be confused with qualitatively observed or quantitatively analyzed washout of contrast. The authors found that the lesion still hyperenhanced overall at this 60 s time (the ''washout phase'') relative to background renal parenchyma, with a cutoff of the whole lesion enhancing >8.52% more than background renal cortex at 60 s was specific for malignancy [62]. Of note, we have not replicated this final finding; in our subjects, we have seen delayed phase hypoenhancement (''washout'') of ccRCCs relative to normal renal parenchyma, with both qualitative (Figs.…”
Section: Quantitative Imagingmentioning
confidence: 99%
“…The second criterion evaluated the lesion as a whole at 60 s post-injection; this was termed the ''washout phase,'' a time point not to be confused with qualitatively observed or quantitatively analyzed washout of contrast. The authors found that the lesion still hyperenhanced overall at this 60 s time (the ''washout phase'') relative to background renal parenchyma, with a cutoff of the whole lesion enhancing >8.52% more than background renal cortex at 60 s was specific for malignancy [62]. Of note, we have not replicated this final finding; in our subjects, we have seen delayed phase hypoenhancement (''washout'') of ccRCCs relative to normal renal parenchyma, with both qualitative (Figs.…”
Section: Quantitative Imagingmentioning
confidence: 99%
“…Cai Y et al [45] showed that early washout in the area of maximal intensity inside of the lesion and prolonged washout in whole area of the lesion are suggestive for RCC. This behavoir seems to be the imaging expression of heterogeneous angiogenesis.…”
Section: Quantitative Imagingmentioning
confidence: 99%
“…This behavoir seems to be the imaging expression of heterogeneous angiogenesis. The authors recommended to combine the hyper-enhancement in the wash-in phase with relative earlier washout of the maximal intensity area in the interior of the lesion to increase the specificity for diagnosing RCC [45].…”
Section: Quantitative Imagingmentioning
confidence: 99%
“…The optimal length of time to observe renal mass enhancement has not been established, but we obtain cines for at least 2 min, so that enhancement can be observed to well past nephrographic phase. From the cine, a time-intensity curve (TIC) can be created, from which quantitative perfusion parameters can be extracted [18,23,24].…”
Section: Time-intensity Curve Analysismentioning
confidence: 99%